Semiconductor nanocrystals and silicate nanoparticles - Peng, Xiaogang. (Structure and bonding, 2005)
A.J. Bard, Z. Ding, N. Myung: Electrochemistry and electrogenerated chemiluminescence of semiconductor nanocrystals in solutions and in films - P. Guyot-Sionnest: Intraband spectroscopy and semiconductor nanocrystals - X. Peng, J. Thessing: Controlled synthesis of high quality semiconductor nanocrystals - D. Santamaria-Pérez, A. Vegas, F. Liebau: The zintl-klemm concept applied to cations in oxides. ii. the structures of silicates.